Dynamics of Rural Communities Under Climate Change. (6th August 2016) - Lugo‐Morin, Diosey Ramon
Abstract: This paper is a critical analysis with two main objectives: to reflect on climate change and demonstrate the importance of adaptive capacities of social actors in rural areas; and to establish how ethnocompetitiveness is fundamental in the mentioned adaptive process. The analysis highlights two key elements that are part of a functional ethnocompetitiveness: local knowledge and management of land resources, allowing for the generation of adaptive capacities to address the inherent biophysical changes associated with climatic variations. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment